The quality of stakeholder engagement disclosures in sustainability reports: a preliminary study from Indonesia / Juniata Gunawan and Rika Yudani - Gunawan, Juniata; Yudani, Rika (Universiti Teknologi MARA Cawangan Sarawak, 2017)
The emerging of sustainability reports reflects the company's efforts in implementing greater transparency. A sustainability report reviews the company’s performances in three parameters: economic, environmental, and social, in which stakeholder engagement is one of the most important elements. However, stakeholder-engagement practices are considered still far from expectation. Information disclosed by a company is not enough to meet the information needed by the public. This study aims to determine the level of quality of stakeholder engagement disclosures in sustainability reports. The quality of disclosure was reviewed by four aspects: ‘Report Content’, ‘Stakeholder Representation’, ‘Stakeholder Engagement’, and ‘Channel and Methods of Stakeholder Engagement’. The content analysis was applied to evaluate the quality of these disclosures and to determine the class ranks of low, moderate, high, and very high. Samples were obtained from 28 sustainability reports which had been consistently published by 7 companies in Indonesia during the period of 2008-2011. The results show that the level of quality of stakeholder engagement disclosures in Indonesian sustainability reports is generally considered moderate. The ‘Employee’ seems to be the major stakeholder which was disclosed widely and it has a relatively strong power to influence a company’s decision